(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Sleep is a complex biological pattern consisting of period of temporary unconsciousness. Sleep deprivation often leads to serious physical and mental health consequences. Medical college students often sacrifice sleep to comply with their demanding academic schedule which may influence their health and academic performance. Objective: To observe sleep patterns in pre-clinical (first and second year) students of MBBS course of Armed Forces Medical College, Dhaka, Bangladesh. Materials and Methods: This cross-sectional study was conducted during the period of March 2021 to July 2021 among 233 respondents. Two validated scales were used to assess quality of sleep and daytime sleepiness: 1) Pittsburgh Sleep Quality Index (PSQI) and 2) Epworth Sleepiness Scale (ESS). Results: Sleep patterns observed in the study-group revealed that more than quarter of the medical students of pre-clinical MBBS course are having insufficient sleep, delayed sleep onset with excessive day time sleepiness. Conclusion: The students should be made aware of the undesirable consequences of improper sleep habits so that they may inculcate healthy sleep practices in their day-to-day life and thus enjoy natural human circadian rhythm and cope up with their busy academic schedule with sound physical and mental health. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 61-66